(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Annotation. Introduction. The article analyzes the existing problems of budgetary control of public procurement in Ukraine in modern conditions, unresolved issues of public procurement after the entry into force the new version of the Law of Ukraine "On Public Procurement", examines the problems of bidders and customers, analyzes strengths and weaknesses in the activities of state control structures for conducting tender procedures, possible losses for the economy of our country in the case of the introduction the bill on the localization of public procurement in Ukraine. Results. Promising direction for the development of public procurement in Ukraine should be the improvement of the Prozorro system and its supplementation with various forms of public control over the conduct of these procurements at all levels. It is proved that a promising direction in the development of public procurement is also the improvement of the Prozorro Market system. The problem is that public control in the field of public procurement is not yet widespread in Ukraine. This is hindered by the lack of financial literacy of the majority citizens, which should be increased through the development of all possible forms of education. Improving the efficiency of the use of public finances in Ukraine requires a significant improvement in the training of staff in budget organizations that generate budget inquiries, as many of them do not have the appropriate education and experience. Significant problem remains the fact that the main indicator for the field of public procurement is still the price, and the indicator of the life cycle of goods is almost not used (as well as other non-price criteria). A difficult problem when applying the cost of the life cycle of goods in public procurement is that the customer independently decides on the feasibility of using it to evaluate tenders. He also chooses the types of costs that are important to him, which will be taken into account when calculating the cost of the life cycle of goods. Conclusions.To strengthen financial control in the field of public procurement, it would be appropriate to use more widely non-price criteria, which are measured not only by the difference between the expected cost of procurement, but also the environmental friendliness of the subject of procurement in the broadest sense. A promising area of public procurement regulation may be the improvement of financial control mechanisms and identify all costs when evaluating the cost of the product life cycle, but it requires substantial retraining customers of the tender. Promising ways to solve existing problems in conducting public procurement in our country, taking into account world experience is substantiated in the article. The mechanism of public procurement in Ukraine must be adapted primarily to EU requirements, which will allow our country in the future to raise questions about joining this organization. This is contradicted by the desire of many government officials and big business to adopt a law on the localization of public procurement in Ukraine, which is contrary to EU norms.